Nickel-copper catalyst and preparation method and application thereof

The nickel-copper catalyst is prepared by using porous carbon/molybdenum disulfide carrier and carrier impregnation method, and the problems of high preparation cost and long cycle in the prior art are solved, and low-cost, high-strength and high-selectivity catalyst preparation is achieved, which is suitable for Preparation of high purity gamma-butyrolactone.

CN119488916APending Publication Date: 2025-02-21POLYCARBONATE OXYGEN NEW MATERIAL TECH (WUXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411658140.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing nickel-based catalysts are costly and have a long preparation cycle during the preparation process, and it is difficult to accurately control the production volume of the active center, which cannot meet the needs of large-scale industrial applications.

Method used

A nickel-copper catalyst was prepared by a support impregnation method using porous carbon/molybdenum disulfide as a support, and a catalyst with high strength and high selectivity was prepared in combination with heat treatment, aging, drying and reducing steps.

Benefits of technology

It realizes the low-cost and efficient preparation of nickel-copper catalysts. The catalyst has ultra-high strength and high selectivity of ≥400N/cm, and is suitable for the preparation of high-purity γ-butyrolactone with selective hydrogenation of malic anhydride.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005142599380000021
    Figure FDA0005142599380000021
Patent Text Reader

Abstract

The invention relates to a nickel-copper catalyst and a preparation method and application thereof. According to the cluster size of the nickel-copper catalyst, the length ranges from 80 nm to 150 nm, the width ranges from 30 nm to 100 nm, and the thickness ranges from 10 nm to 30 nm; the particle strength of the nickel-copper catalyst is greater than or equal to 400N / cm. The preparation method of the nickel-copper catalyst comprises the following steps: stirring and mixing asphalt and molybdenum disulfide; under an oxygen condition, carrying out heat treatment on the obtained mixture to obtain a porous carbon / molybdenum disulfide material carrier; dissolving a nickel precursor compound, a copper precursor compound and a hydrophobic compound in water to obtain a mixed solution; dipping the obtained porous carbon / molybdenum disulfide material carrier in the obtained mixed solution to obtain a catalyst intermediate; and carrying out aging, drying and reduction treatment on the obtained catalyst intermediate to obtain the nickel-copper catalyst. The nickel-copper catalyst provided by the invention has high strength and high selectivity, and can be used for preparing high-purity gamma-butyrolactone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a nickel-copper catalyst and a preparation method and application thereof. Background Art

[0002] Catalytic hydrogenation is widely used in the fields of medicine, oil refining, fine chemicals, etc., and is an important part of the process technology of the modern chemical industry. Hydrogenation catalysts are mainly precious metal catalysts and nickel-based non-metallic catalysts. Among them, precious metal catalysts have high catalytic activity and excellent selectivity, and play an important role in the field of catalytic hydrogenation, but due to their high cost, they cannot be used on a large scale. Among non-precious metals, nickel metal has high catalytic activity and selectivity for hydrogen, as well as its relatively low price, and has been widely used in the field of industrial catalytic hydrogenation. The preparation methods of nickel-based catalysts include co-precipitation method, reduction method, sol-gel method, volume impregnation method, etc.

[0003] Co-precipitation method: heat the catalyst carrier and dispersant in deionized water, then add nickel compound solution and precipitant, age, filter, wash and dry. The catalyst prepared by this method has high catalytic activity and selectivity, but it is difficult to accurately control the production of active centers. Reduction method: impregnate nickel and phosphorus compounds with the carrier, dry, roast and reduce in hydrogen atmosphere in sequence. This method is simple to prepare industrially, but the preparation temperature is high and the preparation time is long. Sol-gel method: add a solution containing a complexing agent dropwise to an aqueous solution containing nickel, stir to generate a sol, heat to form a gel, bake and grind. The active ingredients in this preparation process are more evenly dispersed, but the preparation cost is high and the preparation cycle is long. Volume impregnation method: impregnate the carrier into an aqueous solution containing nickel compounds, dry and roast in sequence. This method has the advantages of low raw material consumption and low cost.

[0004] Therefore, there is an urgent need to provide a low-cost nickel-copper catalyst with high strength and high selectivity. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a nickel-copper catalyst and a preparation method and application thereof. The nickel-copper catalyst prepared by the carrier impregnation method of the present invention has high strength and high selectivity. The catalyst can be used for selective hydrogenation of maleic anhydride to prepare high-purity γ-butyrolactone. Maleic anhydride molecules have one C=C bond and two C=O bonds. Under certain catalytic conditions, selective deep hydrogenation of the C=C bonds will sequentially prepare γ-butyrolactone. To prepare high-purity γ-butyrolactone, it is necessary to control the hydrogenation stage where the hydrogenation reaction precisely stays to maintain controllable high-selectivity hydrogenation.

[0006] The present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is a nickel-copper catalyst, the cluster size of which is: 80nm-150nm in length, 30nm-100nm in width, and 10nm-30nm in thickness; and the particle strength of the nickel-copper catalyst is ≥400N / cm.

[0008] In one embodiment of the present invention, the nickel loading in the nickel-copper catalyst is 30 wt% to 60 wt%, the copper loading is 1 wt% to 5 wt%, and the content of the hydrophobic compound is 0.01 wt% to 0.2 wt%.

[0009] The second object of the present invention is to provide a method for preparing the nickel-copper catalyst, comprising the following steps:

[0010] S1, stirring and mixing asphalt and molybdenum disulfide; heat-treating the obtained mixture under oxygen conditions to obtain a porous carbon / molybdenum disulfide material carrier;

[0011] S2, dissolving the nickel precursor compound, the copper precursor compound and the hydrophobic compound in water to obtain a mixed solution;

[0012] S3, impregnating the porous carbon / molybdenum disulfide material carrier obtained in step S1 into the mixed solution obtained in step S2 to obtain a catalyst intermediate;

[0013] S4, aging, drying and reducing the catalyst intermediate obtained in step S3 to obtain the nickel-copper catalyst.

[0014] In one embodiment of the present invention, in step S1, the mass average molecular weight of the asphalt is 600 to 2000, and the molecular weight distribution is 1.2 to 1.4;

[0015] And / or, the molybdenum disulfide is a nanosheet structure with 5 to 20 layers.

[0016] In one embodiment of the present invention, in step S1, the mass ratio of the asphalt to molybdenum disulfide is 1:5 to 5:1;

[0017] And / or, the heat treatment conditions are: heat treatment at 200°C to 400°C for 3h to 8h.

[0018] In one embodiment of the present invention, the pore volume of the porous carbon / molybdenum disulfide material carrier is 0.2 mL / g to 0.7 mL / g;

[0019] And / or, the particle size of the porous carbon / molybdenum disulfide material carrier is 3 mm to 5 mm;

[0020] And / or, the bulk density of the porous carbon / molybdenum disulfide material carrier is 750 kg / m 3 ~1100kg / m3 In one embodiment of the present invention, in step S2, the nickel precursor compound is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate.

[0021] In one embodiment of the present invention, in step S2, the copper precursor compound is selected from one or more of copper chloride, copper nitrate and copper sulfate.

[0022] In one embodiment of the present invention, in step S2, the structural formula of the hydrophobic compound is Where n≥6.

[0023] In one embodiment of the present invention, in step S2, the mass ratio of the nickel precursor compound, the copper precursor compound and the hydrophobic compound is 50-99:0.1-20:0.01-1.

[0024] In one embodiment of the present invention, step S2 further includes adding an acid solution; after the nickel precursor compound, the copper precursor compound and the hydrophobic compound are fully mixed in the aqueous solution, if there is any undissolved solid, 1 mol / L to 6 mol / L nitric acid solution may be added.

[0025] In one embodiment of the present invention, in step S4, the aging conditions are: aging at 50°C to 80°C for 12h to 16h;

[0026] And / or, the drying conditions are: 100° C. to 140° C., and the drying time is 10 h to 14 h.

[0027] In one embodiment of the present invention, in step S4, the reduction conditions are: reduction at 160°C to 200°C for 6h to 10h under hydrogen and normal pressure. , This makes the nickel-copper catalyst have hydrogenation activity.

[0028] The third object of the present invention is to provide the use of the nickel-copper catalyst in the preparation of gamma-butyrolactone.

[0029] In the nickel-copper catalyst of the present invention, nickel and copper exist in the form of atoms, which are adsorbed on the carrier by physical adsorption, and the catalytic active center clusters exist in the pores of the carrier, both on the surface and inside.

[0030] The porous carbon / molybdenum disulfide carrier of the present invention, due to the layered structural characteristics of molybdenum disulfide, when the carrier is subjected to high temperature treatment, the asphalt will extend along the layered voids, and then undergo dehydration, de-organic matter and other processes at a certain temperature to form a layered carbon structure, which is firmly combined with molybdenum disulfide and produces a large number of pore structures, which is conducive to the dispersion of active metal components. At the same time, this composite carrier structure naturally has a very high mechanical strength, and it is easy to achieve a particle strength of ≥400N / cm, while the particle strength of traditional alumina is difficult to achieve this. The mechanical strength of alumina particles of commercial catalyst carriers can generally reach 100N / cm.

[0031] The above technical solution of the present invention has the following advantages compared with the prior art:

[0032] (1) The catalyst used in the present invention uses porous carbon / molybdenum disulfide as a carrier. The catalyst carrier itself has a certain hydrogenation activity, which can promote the improvement of reaction activity, thereby reducing the reaction temperature, improving the reaction selectivity, and further improving the purity of the product.

[0033] (2) The catalyst prepared by the present invention has an ultra-high strength of ≥400 N / cm, and the metal is not easily lost during the reaction, which plays a key role in the synthesis of high-purity γ-butyrolactone.

[0034] (3) The catalyst used in the present invention uses a hydrophobic compound as an additive, which can make the product γ-butyrolactone desorb from the catalyst surface as quickly as possible. On the one hand, it can accelerate the reaction rate, and on the other hand, it can avoid further reaction of the product on the catalyst surface, thereby achieving the ultimate goal of high product purity. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0036] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0037] The detection method used in the present invention is as follows:

[0038] (1) The purity and impurity content of the product were tested by gas chromatography, with a gas chromatography column HP-5 (30m×320μm×0.25μm) and a FID detector. The column temperature conditions were initial temperature 60℃, first-order termination temperature 90℃, heating rate 15℃ / min, maintained for 2min, second-order termination temperature: 230℃, heating rate 10℃ / min, injection port temperature 260℃, split ratio 100:1, injection volume: 0.2μL, hydrogen flow rate: 30mL / min, nitrogen flow rate: 25mL / min. Using acetone as solvent, standard curves of maleic anhydride, succinic anhydride, tetrahydrofuran, γ-butyrolactone and 1,4-butanediol were established.

[0039] (2) Carry out catalyst strength test in accordance with HG / T 2782 standard.

[0040] Example 1

[0041] This embodiment provides a preparation method and application of a nickel-copper catalyst, which are as follows:

[0042] Preparation of nickel-copper catalyst: weigh 50.00g of basic nickel carbonate, 159.5mL (5mol / L) of dilute nitric acid solution, 4.58g of copper nitrate, 0.30g of sodium dodecyl sulfate, and 500.00g of deionized water, stir at 45°C until all solids are dissolved to obtain a nickel-copper solution; stir and mix asphalt and molybdenum disulfide in a mass ratio of 1:1, heat treat at 300°C for 4h under oxygen conditions to prepare a porous carbon / molybdenum disulfide carrier with a pore volume of 0.5mL / g and a particle size of 5mm; immerse the obtained porous carbon / molybdenum disulfide carrier in the nickel-copper solution, age the mixture at 60°C for 14h under stirring, dry it at 120°C for 12h, load it into tubes, and reduce it under hydrogen conditions at 200°C for 6h to obtain a nickel-copper catalyst.

[0043] The obtained nickel-copper catalyst is used for hydrogenation reaction of maleic anhydride to separate and obtain the product gamma-butyrolactone with a purity of ≥99.990%.

[0044] Example 2

[0045] This embodiment provides a preparation method and application of a nickel-copper catalyst, which is similar to Embodiment 1, except that:

[0046] The nickel-copper catalyst was prepared by replacing basic nickel carbonate with nickel nitrate.

[0047] The obtained nickel-copper catalyst is used for hydrogenation reaction of maleic anhydride to separate and obtain the product gamma-butyrolactone with a purity of ≥99.990%.

[0048] Example 3

[0049] This embodiment provides a preparation method and application of a nickel-copper catalyst, which is similar to Embodiment 1, except that:

[0050] The copper nitrate was replaced by copper chloride to prepare a nickel-copper catalyst.

[0051] The obtained nickel-copper catalyst is used for hydrogenation reaction of maleic anhydride to separate and obtain the product gamma-butyrolactone with a purity of ≥99.990%.

[0052] Comparative Example 1

[0053] This comparative example provides a preparation method and application of a nickel-based catalyst, which are as follows:

[0054] Preparation of nickel-based catalyst: weigh 50.00g of basic nickel carbonate, 159.5mL (5mol / L) of dilute nitric acid solution, 0.30g of sodium dodecyl sulfate, and 500.00g of deionized water, stir at 45°C until all solids are dissolved to obtain a nickel solution; stir and mix asphalt and molybdenum disulfide in a mass ratio of 1:1, heat treat at 300°C for 4h under oxygen conditions to prepare a porous carbon / molybdenum disulfide carrier with a pore volume of 0.5mL / g and a particle size of 5mm; impregnate the obtained porous carbon / molybdenum disulfide carrier in the nickel solution, age the mixture at 60°C for 14h under stirring, and then dry it at 120°C for 12h, load it into tubes, and reduce it under hydrogen conditions at 200°C for 6h to obtain a nickel-based catalyst.

[0055] The obtained nickel-copper catalyst is used for hydrogenation reaction of maleic anhydride to separate and obtain the product gamma-butyrolactone with a purity of less than 90%.

[0056] Comparative Example 2

[0057] This comparative example provides a preparation method and application of a nickel-based catalyst, which are as follows:

[0058] Preparation of nickel-based catalyst: weigh 50.00g of basic nickel carbonate, 159.5mL (5mol / L) of dilute nitric acid solution, 4.58g of copper nitrate, and 500.00g of deionized water, stir at 45°C until all solids are dissolved to obtain a nickel-copper solution; stir and mix asphalt and molybdenum disulfide in a mass ratio of 1:1, heat treat at 300°C for 4h under oxygen conditions to prepare a porous carbon / molybdenum disulfide carrier with a pore volume of 0.5mL / g and a particle size of 5mm; impregnate the obtained porous carbon / molybdenum disulfide carrier in the nickel-copper solution, age the mixture at 60°C for 14h under stirring, and then dry it at 120°C for 12h, load it into tubes, and reduce it under hydrogen conditions at 200°C for 6h to obtain a nickel-based catalyst.

[0059] The obtained nickel-copper catalyst is used for hydrogenation reaction of maleic anhydride to separate and obtain the product gamma-butyrolactone with a purity of less than 80%.

[0060] Comparative Example 3

[0061] This comparative example provides a preparation method and application of a nickel-based catalyst, which are as follows:

[0062] Preparation of nickel-based catalyst: weigh 50.00g of basic nickel carbonate, 159.5mL (5mol / L) of dilute nitric acid solution, and 500.00g of deionized water, stir at 45°C until all solids are dissolved to obtain a nickel solution; stir and mix asphalt and molybdenum disulfide in a mass ratio of 1:1, heat treat at 300°C for 4h under oxygen conditions to prepare a porous carbon / molybdenum disulfide carrier with a pore volume of 0.5mL / g and a particle size of 5mm; impregnate the obtained porous carbon / molybdenum disulfide carrier in the nickel solution, age the mixture at 60°C for 14h under stirring, and then dry it at 120°C for 12h, load it into tubes, and reduce it under hydrogen conditions at 200°C for 6h to obtain a nickel-based catalyst.

[0063] The obtained nickel-copper catalyst is used for hydrogenation reaction of maleic anhydride to separate and obtain the product gamma-butyrolactone with a purity of less than 5%.

[0064] Comparative Example 4

[0065] This comparative example provides a preparation method and application of a nickel-based catalyst, which are as follows:

[0066] Preparation of nickel-based catalyst: Weigh 50.00g of basic nickel carbonate, 159.5mL (5mol / L) dilute nitric acid solution, 4.58g of copper nitrate, 0.30g of sodium dodecyl sulfate, and 500.00g of deionized water and stir at 45°C until all solids are dissolved to obtain a nickel-copper solution; heat treat the asphalt at 300°C for 4h under oxygen conditions to obtain porous carbon with a pore volume of 0.5mL / g and a particle size of 5mm. The obtained porous carbon / molybdenum disulfide carrier is impregnated in the nickel-copper solution, and the mixture is aged at 60°C for 14h under stirring, and then dried at 120°C for 12h, loaded into the tube, and reduced at 200°C for 6h under hydrogen conditions to obtain a nickel-based catalyst.

[0067] The obtained nickel-copper catalyst is used for hydrogenation reaction of maleic anhydride to separate and obtain the product γ-butyrolactone with a purity of less than 2%.

[0068] Test Case

[0069] The strength of the catalysts prepared in the examples and comparative examples was tested according to the HG / T 2782 standard. The test results are shown in Table 1 below:

[0070] Table 1

[0071] catalyst Strength (N / cm) Example 1 453.3 Example 2 451.8 Example 3 457.2 Comparative Example 1 453.8 Comparative Example 2 454.6 Comparative Example 3 451.5 Comparative Example 4 205.1

[0072] It can be seen from Table 1 that the strength of the supported catalyst prepared in the example exceeds 450 N / cm. By combining high-strength molybdenum disulfide with porous carbon, the strength of the supported catalyst can be greatly improved.

[0073] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A nickel-copper catalyst, characterized in that The nickel-copper catalyst comprises a catalytically active center cluster composed of nickel, copper and a hydrophobic compound; the size of the catalytically active center cluster is: 80nm to 150nm in length, 30nm to 100nm in width, and 10nm to 30nm in thickness; The particle strength of the nickel-copper catalyst is ≥400N / cm.

2. The nickel-copper catalyst according to claim 1, characterized in that The nickel loading in the nickel-copper catalyst is 30 wt% to 60 wt%, the copper loading is 1 wt% to 5 wt%, and the content of the hydrophobic compound is 0.01 wt% to 0.2 wt%.

3. The method for preparing the nickel-copper catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1, stirring and mixing asphalt and molybdenum disulfide; heat-treating the obtained mixture under oxygen conditions to obtain a porous carbon / molybdenum disulfide material carrier; S2, dissolving the nickel precursor compound, the copper precursor compound and the hydrophobic compound in water to obtain a mixed solution; S3, impregnating the porous carbon / molybdenum disulfide material carrier obtained in step S1 into the mixed solution obtained in step S2 to obtain a catalyst intermediate; S4, aging, drying and reducing the catalyst intermediate obtained in step S3 to obtain the nickel-copper catalyst.

4. The preparation method according to claim 3, characterized in that: In step S1, the mass ratio of asphalt to molybdenum disulfide is 1:5 to 5:1; And / or, the heat treatment conditions are: heat treatment at 200°C to 400°C for 3h to 8h.

5. The preparation method according to claim 3, characterized in that: In step S2, the nickel precursor compound is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate.

6. The preparation method according to claim 3, characterized in that: In step S2, the copper precursor compound is selected from one or more of copper chloride, copper nitrate and copper sulfate.

7. The preparation method according to claim 3, characterized in that: In step S2, the structural formula of the hydrophobic compound is Where n≥6.

8. The preparation method according to claim 3, characterized in that: In step S2, the mass ratio of the nickel precursor compound, the copper precursor compound and the hydrophobic compound is 50-99:0.1-20:0.01-1.

9. The preparation method according to claim 3, characterized in that: In step S4, the reduction conditions are: reduction at 160° C. to 200° C. for 6 h to 10 h.

10. Use of the nickel-copper catalyst according to claim 1 or 2 in the preparation of γ-butyrolactone.